1990
DOI: 10.1016/0248-4900(90)90345-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate deposits in domes of human pancreatic adenocarcinoma (Capan‐1) cell cultures

Abstract: Human pancreatic cells of the Capan-1 line form domes in culture during the stationary growth stage. The domes are thought to be a result of the transport of water and electrolytes by the Capan-1 cells. In older Capan-1 cultures, the epithelial sheets formed thickenings from several layers of cells of which the outermost ones were joined by tight type junctions. In the intracellular space, deposits of insoluble calcium salts were observed. Culture of Capan-1 cells in the presence of fibroblasts prolonged survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…To evaluate the directional transport of NSP4 in the polarized kidney and intestinal cell lines, the cells were seeded at a density of 1 × 10 5 cells/cm 2 on Transwell permeable membrane supports (Corning Costar, Acton, MA) and separately on plastic at the same density to monitor confluency and the formation of domes, which are indicative of directional transepithelial water and electrolyte transport [58,59]. Transepithelial resistance (TER) was monitored prior to, during and post RV infection using a Millicel-ERS volt-ohmmeter according to the manufacturer's instructions (Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the directional transport of NSP4 in the polarized kidney and intestinal cell lines, the cells were seeded at a density of 1 × 10 5 cells/cm 2 on Transwell permeable membrane supports (Corning Costar, Acton, MA) and separately on plastic at the same density to monitor confluency and the formation of domes, which are indicative of directional transepithelial water and electrolyte transport [58,59]. Transepithelial resistance (TER) was monitored prior to, during and post RV infection using a Millicel-ERS volt-ohmmeter according to the manufacturer's instructions (Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…They were found as clusters of needle-like crystals surrounded by amorphous material. EDX and electronic diffraction analysis showed that they were Ca-P crystals close to apatite composition (Table 5), which have already been described generally in pathological cases of animal tissues (Hering et al, 1987;Hollande et al, 1990;Cantet et al, 2001). To our knowledge, calcium phosphate crystals have not yet been described in plants.…”
Section: Damages On V Faba L As a Response To Metal Contamination: mentioning
confidence: 99%
“…The crystalline structures observed in CF tissues [10,16,24,25,29,32] may well have been calcium phosphate in an apatite-like structure. It is likely that such crystals form at a late stage of cystic fibrosis as has been observed in other diseases [1,17,32]. The crystalline aggregates in bronchial segments and alveoli that we observed could be accounted for by the fact that the tissue came from a child with an advanced stage of the disease.…”
Section: Discussionmentioning
confidence: 57%